Probing the effects of Retinoblastoma Binding Protein 6 (RBBP6) knockdown on the sensitivity of cisplatin in cervical cancer cells - Moela, Pontsho (University of Pretoria, 2022)
Dissertation (MSc (Genetics))--University of Pretoria, 2022.